HIV prevalence and HIV clinical outcomes of transgender and gender‐diverse people in England. Issue 2 (26th October 2020) - Kirwan, PD; Hibbert, M; Kall, M; Nambiar, K; Ross, M; Croxford, S; Nash, S; Webb, L; Wolton, A; Delpech, VC
Abstract : Objectives: We provide the first estimate of HIV prevalence among trans and gender‐diverse people living in England and compare outcomes of people living with HIV according to gender identity. Methods: We analysed a comprehensive national HIV cohort and a nationally representative self‐reported survey of people accessing HIV care in England (Positive Voices). Gender identity was recorded using a two‐step question co‐designed with community members and civil society. Responses were validated by clinic follow‐up and/or self‐report. Population estimates were obtained from national government offices. Results: In 2017, HIV prevalence among trans and gender‐diverse people was estimated at 0.46–4.78 per 1000, compared with 1.7 (95% credible interval: 1.6–1.7) in the general population. Of 94 885 people living with diagnosed HIV in England, 178 (0.19%) identified as trans or gender‐diverse. Compared with cisgender people, trans and gender‐diverse people were more likely to be London residents (57% vs . 43%), younger (median age 42 vs . 46 years), of white ethnicity (61% vs . 52%), under psychiatric care (11% vs . 4%), to report problems with self‐care (37% vs . 13%), and to have been refused or delayed healthcare (23% vs . 11%). Antiretroviral uptake and viral suppression were high in both groups. Conclusions: HIV prevalence among trans and gender‐diverse people living in England is relatively low compared with international estimates. Furthermore, no inequalities were observed with regard to HIV care. Nevertheless, trans and gender‐diverse people with HIV report poorer mental health and higher levels of discrimination compared with cisgender people.